Effect of Calcium On Barley Tolerance To Increased Concentration Of NaCl - Al- Rubaiee, F.A.A. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
This study was conducted to the college of education ( Ibn Al- Haitham ) – University of Baghdad ( 2001 – 2002 ) to evaluate the barley ( Hordeum vulgare L. ) response to effect of salinity and salinity with calcium in the growth medium . Seed germination was carried out in petridishs by using the nutrient solution of Arnon and Hoagland containing different concentrations of NaCl ( 0,50,100 and 150 mM ) and these concentrations with 5mM calcium sulfate . Plant growth was continued in hydroponic culture in green house for 4 weeks . Results showed that salinity caused a decrease in the percentage of germination, plant growth , protein content and stability of the plasma membrane significantly reduced by adding calcium in the growth medium . Results supported the importance of calcium in tolerance of crope plants to saline stress